Progressive Trends in Variation Form: Robert Schumann’s Piano Sonata in F Minor, Op. 14, Quasi Variazioni - Hiu-Wah Au (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
Entitled Quasi Variazioni, the third movement of Schumann’s Piano Sonata in F Minor, op. 14 (1835–36), displays features that are not usually associated with variation form. In a typical eighteenth- and nineteenth-century variation set, the theme is usually a self-contained unit, whose form and voice leading are often preserved throughout the set. But in this Schumann movement, the theme presents an unusual, tripartite ABC form, its half-cadence ending evoking the tradition of continuous variation. Along with the theme’s peculiar formal plan, the variations also diverge markedly from the theme’s form and middleground structure. These differences are engendered by Schumann’s special handling of the theme. Instead of regarding the theme as an entity to be varied as a whole, Schumann treats its motivic, voice-leading, and harmonic elements as discrete components to be developed independently of one another. By reworking and combining these elements, Schumann progressively transforms the form and middleground of the theme. Significantly, these changes create motivic, harmonic, and voice-leading connections among the variations. These connections not only create a sense of development from one variation to another, but also articulate the large-scale organization of the entire set.